Clinical significance of receptor shedding-platelet GPVI as an emerging diagnostic and therapeutic tool. (19th May 2017) - Chatterjee, Madhumita; Gawaz, Meinrad
Abstract: Platelet membrane bedecked with a wide array of receptors offers a platform to regulate platelet responsiveness, thrombotic propensity, inflammatory disposition, and immune reactivity under diverse pathophysiological conditions. Ectopic proteolytic cleavage of such receptors irreversibly inactivates receptor-mediated intracellular signaling governing cellular functions, further releases soluble fragments into circulation which might modulate functions of target cells. Glycoprotein VI-(GPVI) is a membrane glycoprotein expressed in platelets and megakaryocytes. Platelet GPVI surface expression is enhanced following acute ischemic events like myocardial infarction and cerebral stroke, serves as an imminent diagnostic tool independent of markers of tissue necrosis, and is associated with poor prognosis. Platelets undergo GPVI shedding and thereby contribute to soluble plasma levels of sGPVI, with distinct diagnostic and prognostic attributes. This review summarizes the functional significance and mechanistic basis whereby GPVI surface availability is up- or downregulated on platelets and the impact of GPVI in diagnostic, prognostic, and therapeutic strategies in diseases where platelets play a regulatory role. Further, we also highlight how novel non-invasive platelet-based diagnostic and therapeutic strategies have evolved utilizing GPVI for lesion-directed antithrombotic therapy or to counteract atherosclerotic disposition to ameliorate care of patients particularly in the context of cardio-cerebro-vascular medicine.